1997
DOI: 10.1177/106002809703100603
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Intravenous Phosphate Replacement in Critically Ill Patients

Abstract: The administration of potassium phosphate 15 mmol to critically ill patients with mild-to-moderate hypophosphatemia over 3 hours is both effective and safe. The administration of potassium phosphate 30 mmol to severely hypophosphatemic patients was safe but achieved normalization of serum phosphate in a minority of patients. Either a higher dose or the subsequent administration of more potassium phosphate may be required to normalize serum phosphate concentrations. Once normalization has occurred, there is a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
1
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(22 citation statements)
references
References 18 publications
0
20
1
1
Order By: Relevance
“…A prospective comparative cohort study of 27 patients with severe hypophosphataemia showed the safety of administering 15-30 mmol phosphate over three hours via a central venous catheter in an intensive care unit. 16 However, the researchers reported the need for repeated doses in most patients. Terlevich et al reported efficacy of 50 mmol phosphate infused into a peripheral vein over 24 hours in 30 patients with no pre-existing renal dysfunction on general wards.…”
Section: Body Mass Index (Kg/m 2 ) <16mentioning
confidence: 99%
“…A prospective comparative cohort study of 27 patients with severe hypophosphataemia showed the safety of administering 15-30 mmol phosphate over three hours via a central venous catheter in an intensive care unit. 16 However, the researchers reported the need for repeated doses in most patients. Terlevich et al reported efficacy of 50 mmol phosphate infused into a peripheral vein over 24 hours in 30 patients with no pre-existing renal dysfunction on general wards.…”
Section: Body Mass Index (Kg/m 2 ) <16mentioning
confidence: 99%
“…11,12 With regard to electrolyte repletion, numerous studies have focused on the control of a single electrolyte. [13][14][15][16] To date, 4 studies have evaluated repletion protocols for multiple electrolytes in various intensive care settings. [17][18][19][20] The results of these studies have suggested that use of repletion protocols is more effective than standard approaches to electrolyte repletion.…”
Section: Introductionmentioning
confidence: 99%
“…Intravenous phosphate replacement may be required in these cases to correct the concentration of serum phosphate, thus ameliorating the risk of complications. 2 Although usually multifactorial in origin, the pathogenesis of hypophosphatemia includes the following mechanisms: inadequate phosphate intake, decreased intestinal absorption, gastrointestinal or renal phosphate loss, and redistribution of phosphate into cells. The latter mechanism might be the link between rapidly proliferating cells and severe hypophosphatemia as has been reported in patients suffering from hematological malignancies.…”
mentioning
confidence: 99%